Expressions of Neuregulin 1β and ErbB4 in Prefrontal Cortex and Hippocampus of a Rat Schizophrenia Model Induced by Chronic MK-801 Administration. (28th December 2010) - Feng, Yu; Wang, Xiao-Dong; Guo, Chun-Mei; Yang, Yang; Li, Ji-Tao; Su, Yun-Ai; Si, Tian-Mei
Abstract : Recent human genetic studies and postmortem brain examinations of schizophrenia patients strongly indicate that dysregulation of NRG1 and ErbB4 may be important pathogenic factors of schizophrenia. However, this hypothesis has not been validated and fully investigated in animal models of schizophrenia. In this study we quantitatively examined NRG1 and ErbB4 protein expressions by immunohistochemistry and Western blot in the brain of a rat schizophrenia model induced by chronic administration of MK-801 (a noncompetitive NMDA receptor antagonist). Our data showed that NRG1β and ErbB4 expressions were significantly increased in the rat prefrontal cortex and hippocampus but in different subregions. These findings suggest that altered expressions of NRG1 and ErbB4 might be attributed to the schizophrenia. Further study in the role and mechanism of NRG1 and ErbB4 may lead to better understanding of the pathophysiology for this disorder.